Design and Development of an Automated System to Help with Feeding Infants - Alshahrani, Suhail S; Alfulaij, Abdulrahman Y; Alokaily, Ahmad O. (British Journal of Healthcare and Medical Research, 2024)
Feeding infants is considered one of the biggest challenges for parents, especially in the first three months. Infants under three months old usually must befed every two hours, which can burden many parents, particularly at bedtime. Therefore, this paper develops and validates a cost-effective assistive and automated system to automatically prepare and store a filled feeding bottle during bedtime. A bottle keeper to cool and warm an infant’s bottle is used to store a feeding bottle at the recommended temperature and warm it at set feeding intervals or whenever hunger signs are detected. Several experiments are performed to test and validate the proposed system. The system shows promising results in facilitating infant feeding for parents, especially at bedtime. In addition, the system can help enhance infants’ nutrition.